THE ANALYSIS ON DESCRIPTIVE TEXT PRODUCED BY THE EIGHTH YEAR STUDENT OF SMP N 3 KRADENAN GROBOGAN - RATNASARI, DEWI (2011)
This research paper aims at analyzing descriptive text produced by the eighth year student of SMP N 3 Kradenan Grobogan and the problems faced by the students in writing descriptive text. In this research, the writer uses descriptive research. The object of the study is descriptive text produced by 34 students of the eighth year student of SMP N 3 Kradenan Grobogan. The data of this research are descriptive text produced by 34 students of the eighth year student of SMP N 3 Kradenan Grobogan. The sources of the data are the student's worksheet of writing descriptive text. In this research, the writer carries out document to get the data. The technique for analyzing data are based on generic structure of descriptive text to know the result of descriptive text produced by the eighth year student of SMP N 3 Kradenan Grobogan and significant lexicogrammatical features of descriptive text to know the problems faced by the eighth year student of SMP N 3 Kradenan Grobogan in writing descriptive text. The result of the analysis shows that based on analysis of generic structure of descriptive texts produced by the eighth year student of SMP N 3 Kradenan Grobogan, there are five descriptive texts that are not suitable with the generic structure of descriptive text, because there are some ideas that are out from the topic. Based on analysis of significant lexicogrammatical features of descriptive text, there are four problems faced by the students in writing descriptive text, namely: (a) there are three students that do not focus on the specific participant, (b) there are two students that do not use nominal group, (c) all of the students use attributive and identifying processes, (d) there are two students that do not use simple present tense.